Double balloon esophageal catheter for diagnosis of tracheo-esophageal fistula - KIYAN, GÜRSU (SPRINGER-VERLAG, 2003)
Congenital H-type and recurrent tracheo-esophageal fistulas (TEF) are always difficult to diagnose. For a more accurate diagnosis we designed a new double balloon catheter, which is a modification of esophageal dilatation balloon. The catheter has two balloons to occlude the esophagus proximal and distal to the fistula. The fistula can be identified by passing of the contrast material to the tracheal tree, which was injected into the esophageal segment between the inflated balloons. To prove the efficiency of this catheter, a TEF was created surgically in a New Zealand rabbit. On the postoperative fourteenth day the catheter was tried and the fistula could be visualized easily by injecting the contrast material. We think this technique may be of use in the diagnosis of TEF in children.
Keywords: diagnosis; tracheo-esophageal fistula; RECURRENT TRACHEOESOPHAGEAL FISTULAS